Weighted Estimates for Maximal Commutators of Multilinear Singular Integrals - Dongxiang Chen; Suzhen Mao (Journal of Function Spaces and Applications, 2012)
This paper is concerned with the pointwise estimates for the sharp function of the maximal multilinear commutators TΣb* and maximal iterated commutator TΠb*, generalized by m-linear operator T and a weighted Lipschitz function b. The (Lp1(μ)×⋯×Lpm(μ),Lr(μ1-r)) boundedness and the (Lp1(μ)×⋯×Lpm(μ),Lr(μ1-mr)) boundedness are obtained for maximal multilinear commutator TΣb* and maximal iterated commutator TΠb*, respectively.